Présentation clinique, biologique et ergométrique de six cas d`overtraining syndrome - Brun, J. F.; Varlet-Marie, E.; Faugoin, C.; Mercier, J. (Science & Sports, 2009)
This work aimed at describing clinical and laboratory characteristics of the overtraining syndrome in its chronic form (staleness).